Implementation of Hybrid Teaching as a Derivation of COVID-19 (Docentes 2.0 Journal, 2022)
Although digital technologies have tried to be installed in teaching practices for some years, the pandemic has had a strong impact worldwide on an educational system that was not prepared to assume such a sudden change. The present documentary research is supported by the Humanist paradigm, qualitative approach, narrative-interpretive type, and biographical design to know the recent experiences in which the hybrid model has been used and its possibilities of implementation in high education in Argentina. Due to COVID-19, new proposals for virtual or remote teaching have had to be considered in contexts of uncertainty and permanent change, which has challenged teachers and the educational system in general regarding scheduling a class. The use of technological tools, the optimization of communication channels, and the implementation of new strategies and work dynamics. In the course of these changes, the term “hybrid” began to be used to refer to teaching contexts that alternate face-to-face and virtual teaching. Although it is not a new approach, it is necessary to explore the complexity of its implementation in the current educational context, mainly concerning higher education, and determine the digital skills that teachers must develop. The results showed that universities try to include technology in the classroom, but there is still a long way. The main conclusions reached are teacher training and a shift towards a more student-centered paradigm.
Keywords: Implementation; teachings; higher level; hybrid teaching; COVID-19